Immunomodulatory Properties of Carvone Inhalation and Its Effects on Contextual Fear Memory in Mice - Lasarte-Cia, Aritz; Lozano, Teresa; Pérez-González, Marta; Gorraiz, Marta; Iribarren, Kristina; Hervás-Stubbs, Sandra; Sarobe, Pablo; Rabal, Obdulia; Cuadrado-Tejedor, Mar; García-Osta, Ana; Casares, Noelia; Lasarte, Juan José (Frontiers in Immunology, 2018)
A complex network of interactions exists between the immune, the olfactory and the central nervous systems. Inhalation of different fragrances can affect immunological reactions in response to an antigen but also may have effects on the central nervous system and cognitive activity. We performed an exploratory study of the immunomodulatory ability of a series of compounds representing each of the 10 odour categories or clusters described previously. We evaluated the impact of each particular odour on the immune response after immunization with the model antigen ovalbumin in combination with the TLR3 agonist Poly I:C. We found that some odours behave as immunostimulatory agents, whereas others might be considered as potential immunosuppressant odours. Interestingly, the immunomodulatory capacity was, in some cases, strain-specific. In particular, one of the fragrances, carvone, was found to be immunostimulatory in BALB/c mice and immunosuppressive in C57BL/6J mice, facilitating or impairing viral clearance respectively, in a model of a viral infection with a recombinant adenovirus. Importantly, inhalation of the odour improved the memory capacity in BALB/c mice in a fear conditioning test, while it impaired this same capacity in C57BL/6J mice. The improvement in memory capacity in BALB/c was associated with higher CD3+ T cell infiltration into the hippocampus and increased local expression of mRNA coding for IL-1beta, TNF-alpha and IL-6 cytokines. In contrast, the memory impairment in C57BL/6 was associated with a reduction in CD3 numbers and an increase in IFN-gamma. These data suggest an association between the immunomodulatory capacity of smells and their impact on the cognitive functions of the animals. These results highlight the potential of studying odours as therapeutic agents for CNS-related diseases.